Representation of gender in crime news reports in a daily newspaper / Nursuhaila bte Ibrahim - Nursuhaila, Ibrahim (2013)

(untitled)
Newspaper reports serve as an important influence over public perception and opinion as it is a source of information about the world. There are various sections presented in newspaper such as technology, sports, and entertainment. One of the sections presented is on crime reports whereby the media reports the crime scenario almost every day around the world. The representation of victims, offenders as well as the situation of crime creates concern and awareness in the readers. This study focuses on the analysis of criminal news reports in a local printed newspaper. Its aim is to investigate the representation of gender in crime news reports and examine the language used in reporting the crime. The method employed is qualitative and quantitative while content analysis is used to analyse the data. The theoretical framework is based on the theme of ‘negative image of men’ proposed by Erlendson, J. (2011) and several categories to describe men and women in crime reports. The study reveals that men are cruel and irrational as they are represented in a negative image and women are weak and helpless and portrayed as the ‘ideal victims’. The findings also indicate that the language included descriptive adjectives to describe about the victims, offenders and the situation of crimes. In addition, the news headlines portrayed men as the offenders and women as the victims. Overall, this study provides valuable information regarding crime news reports and is beneficial towards further studies on gender, language and media.